Effects of psychological intervention on empathy fatigue in nurses: A meta-analysis - Chen, Xiaojuan; Chen, Mingdi; Zheng, Huang; Wang, Chaoyu; Chen, Huimin; Wu, Qinglan; Liao, Huizhao; Zhu, Jinru; Lin, Junyan; Ou, Xudong; Zou, Zhihong; Wang, Zhiwei; et al. (Frontiers in Public Health, 2022)
Objective: The purpose of this meta-analysis is to systematically assess the effects of psychological intervention on empathy fatigue among nursing staff. Method: The time frame for the search is from the beginning to April 8th, 2022. Five electronic databases are searched separately. The research team independently performs paper selection, quality assessment, data extraction and analysis for all included studies. PRISMA guidelines are used to report this meta-analysis. Results: A total of seven randomized controlled trials (RCTs) covering 513 nursing staff are included. The meta-analysis results show that the empathy fatigue score (SMD = -0.22, 95% CI: -0.42 ~ -0.02, P = 0.03) and burnout (SMD = -0.37, 95% CI: -0.56 ~ -0.19, P < 0.0001) are lower than the control group. The empathy satisfaction score of the psychological intervention group is higher than that of the control group (SMD = 0.45, 95% CI: 0.27-0.63, P < 0.00001). The differences are statistically significant (P < 0.05). Subgroup analysis finds significant heterogeneity in the impact of different departments on psychological intervention at ≥6 weeks (I2 = 71%, P = 0.01) and < 6 weeks (I2 = 0%, P = 0.75) (P = 0.05). Different departments also show significant heterogeneity in the effects of psychological intervention: ICU (I2 = 73%, P = 0.02), pediatric (I2 = 53%, P = 0.14) and other departments (I2 = 0%, P = 0.63). The differences are statistically significant (P = 0.0007). Conclusion: Psychological intervention has a coordinated improvement effect on empathy fatigue, empathy satisfaction and burnout, and can also improve the quality of life of nursing staff.